Hypoglycaemia Metabolic Gene Panel Testing - Maiorana, Arianna; Lepri, Francesca Romana; Novelli, Antonio; Dionisi-Vici, Carlo (Frontiers in Endocrinology, 2022)
A large number of inborn errors of metabolism present with hypoglycemia. Impairment of glucose homeostasis may arise from different biochemical pathways involving insulin secretion, fatty acid oxidation, ketone bodies formation and degradation, glycogen metabolism, fructose and galactose metabolism, branched chain aminoacids and tyrosine metabolism, mitochondrial function and glycosylation proteins mechanisms. Historically, genetic analysis consisted of highly detailed molecular testing of nominated single genes. However, more recently, the genetic heterogeneity of these conditions imposed to perform extensive molecular testing within a useful timeframe via new generation sequencing technology. Indeed, the establishment of a rapid diagnosis drives specific nutritional and medical therapies. The biochemical and clinical phenotypes are critical to guide the molecular analysis toward those clusters of genes involved in specific pathways, and address data interpretation regarding the finding of possible disease-causing variants at first reported as variants of uncertain significance in known genes or the discovery of new disease genes. Also, the trio’s analysis allows genetic counseling for recurrence risk in further pregnancies. Besides, this approach is allowing to expand the phenotypic characterization of a disease when pathogenic variants give raise to unexpected clinical pictures. Multidisciplinary input and collaboration are increasingly key for addressing the analysis and interpreting the significance of the genetic results, allowing rapidly their translation from bench to bedside.